Where did mountain pine beetle populations in Jasper Park come from? Tracking beetles with genetics - Stephen A.L. Trevoy; Jasmine K. Janes; Felix A.H. Sperling (The Forestry Chronicle)
The invasion of mountain pine beetle (Dendroctonus ponderosae Hopk.) into Alberta has been an ongoing concern for forest management. The beetle’s recent appearance and spread in Jasper National Park now poses ecological and economic threats to forestry in regions to the east. By applying recent advances in genetic typing and analysis, we show that the beetle population in Jasper is comprised of mixed individuals combining genetic signatures of both northern and southern beetles. Coupled with current monitoring methods, genetic markers can be used to identify the origin of novel populations, facilitate precise monitoring of beetle expansion and potentially inform targeted management strategies.